Evaluation of the performance and economic viability of a novel low temperature carbon capture process. (July 2019) - Willson, Paul; Lychnos, George; Clements, Alastair; Michailos, Stavros; Font-Palma, Carolina; Diego, Maria Elena; Pourkashanian, Mohamed; Howe, Joe
Highlights: Novel process avoids cost and performance penalties of conventional cryogenic ones. Use of moving packed bed achieves intensive heat and mass transfer. Cost of various process applications benchmarked against reference MEA cases. New process has 70% lower levelised cost of capture than MEA for smaller cases. Abstract: A novel Advanced Cryogenic Carbon Capture (A3C) process is being developed using low cost but high intensity heat transfer to achieve high CO2 capture efficiencies with a much reduced energy consumption and process equipment size. These characteristics, along with the purity of CO2 product and absence of process chemicals, offer the potential for application across a range of sectors. This work presents a techno-economic evaluation for applications ranging from 3% to 35%vol. CO2 content. The A3C process is evaluated against an amine-based CO2 capture process for three applications; an oil-fired boiler, a combined cycle gas turbine (CCGT) and a biogas upgrading plant. The A3C process has shown a modest life cost advantage over the mature MEA technology for the larger selected applications, and substantially lower costs in the smaller biogas application. Enhanced energy recovery and optimization offer significant opportunities for further reductions in cost.